Resilient Cities: Spatial Planning and Transportation - Arzu Maltaş Erol (Doğal Afetler ve Çevre Dergisi)
Today, cities face multiple crises due to increasing population and construction densities, making them vulnerable. Disasters, pose significant threats to urban areas by disrupting systems and causing serious damage and losses. The concept of resilience has recently gained considerable attention as a solution to these vulnerabilities. In its most general sense, resilience refers to the capacity of a system to quickly recover from adverse effects. A resilient city means that its urban systems have the strength to withstand crises and can rapidly restore themselves to ensure sustainability. Therefore, disaster-resilient cities have the capacity to effectively intervene before, during, and after disasters. Introduced into urban literature since the 1990s, this concept has highlighted disaster-resilient spatial planning to minimize the impacts of disasters. During this process, it has been understood that transportation systems play a significant role in mitigating the destructive effects of disasters on cities. Considering the impacts of disasters on transportation networks, systems, and services, disaster-resilient urban and transportation planning encompass not only the moments during disasters but also the preparation processes before potential disasters. Additionally, these plans, which include the recovery process after disasters, are critical in ensuring the safe evacuation of people and the supply of materials, supporting the continuity of mobility and accessibility, and while reducing damage to cities. This study examines how cities can become more resilient to crises and evaluates the role of disaster management and transportation planning in enhancing urban resilience. Within the scope of the study, the concept of resilient, its features, and the impacts of disasters on spatial planning are first addressed. The conceptual framework for disaster-resilient spatial planning is broadly explained. Subsequently, the importance of transportation planning is discussed, and strategies to create a disaster-resilient transportation system in urban areas are evaluated. In conclusion, the study finds that transportation planning in resilient cities is crucial for increasing resilience to disasters and ensuring public safety.